The informal economy and its impact on tax revenues and economic growth. The case of Peru, Latin America and OECD countries (1995 – 2016) - Boitano, Guillermo (2019)
The main goal of the research will be to determine the size of the informal economy in Peru, Latin America and OCDE countries as well as to estimate the impact of the informal economy on tax revenues and the economic growth. To achieve the goal, the approach is made through MIMIC (multiple-indicator and multiple-cause) model. The main results show that the estimated average size of the informal economy as a percentage of the GDP in Peru is 37.4%, in Latin America is 34%, and in OCDE countries is 19.83%, which represents less than half of the Latin America average.